2008
DOI: 10.1016/j.foreco.2007.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harrowing and fertilisation on understory vegetation and timber production of a Eucalyptus globulus Labill. plantation in Central Portugal

Abstract: Harrowing and fertilisation are common practices at middle rotation in Eucalyptus globulus Labill. plantations in Central Portugal. In order to clarify the effects of such practices on understory vegetation and timber production, a field trial was installed in a 5-year-old first rotation eucalyptus plantation, in a region with mixed oceanic and Mediterranean climatic influences. Four treatments that involved harrowing (H), fertilisation (F), harrowing and fertilisation (HF), and control (C) were tested in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
3
16
1
1
Order By: Relevance
“…In our study area, lower values for native species richness in eucalypt stands have been observed, in agreement with Briones and Ineson (1996) and Carneiro et al (2008), who reported a reduction of floristic diversity in Eucalyptus plantations. Furthermore, the lower values for native species richness in the surveyed eucalypt stands may be promoting alien invasion by decreasing community saturation and biotic resistance, resulting in higher values for alien species richness (Section 3.2 and Fig.…”
Section: Implications Of Forest Changes For Patterns Of Species Diversupporting
confidence: 92%
See 2 more Smart Citations
“…In our study area, lower values for native species richness in eucalypt stands have been observed, in agreement with Briones and Ineson (1996) and Carneiro et al (2008), who reported a reduction of floristic diversity in Eucalyptus plantations. Furthermore, the lower values for native species richness in the surveyed eucalypt stands may be promoting alien invasion by decreasing community saturation and biotic resistance, resulting in higher values for alien species richness (Section 3.2 and Fig.…”
Section: Implications Of Forest Changes For Patterns Of Species Diversupporting
confidence: 92%
“…The prevalence of non-indigenous plant species in forest plantations is probably due to the fact that environmental conditions created by the exotic eucalypt (e.g. soil, Carneiro et al, 2008) are not the most adequate for indigenous forest species, as already reported in other studies (e.g. see Carnus et al, 2003).…”
Section: Implications Of Forest Changes For Patterns Of Species Divermentioning
confidence: 77%
See 1 more Smart Citation
“…However, the increase by the end of rotation period (98 months after treatments), especially in the control, does not agree with previous knowledge of the authors for similar eucalyptus plantations Carneiro et al 2009), given the conditions that hamper the understory development. The different pattern found in the present study may be associated with size increase over time of scattered perennial woody shrubs (such as Ulex spp) and tall Gramineae (such as Pseudarrhenatherum longifolium) (see Carneiro et al 2008).…”
Section: Understory and Litter Layerscontrasting
confidence: 54%
“…Harvest residue management systems (removal or maintenance) are a source of strong current debate, not only because of soil quality considerations, but also the use of residues for bioenergy purposes (Cowie et al, 2006;Stupak et al, 2007), an initiative actively encouraged by Portuguese Forestry Commission (2006, http:// www.afn.min-agricultura.pt/portal/politica-e-planeamento-florestal/enf/estrategia-nacional-para-as-florestas/). Similar to other intensive plantation studies (Tremblay and Larocque, 2001;Archer, 2003), studies on understory vegetation in eucalyptus plantations in Mediterranean conditions have focused on species richness and biodiversity (Fabião et al, 2002;Carneiro et al, 2007Carneiro et al, , 2008. A greater understanding of understory productivity and nutrient dynamics is essential in order to contribute to the development of improved establishment and management strategies, taking into account timber production, environmental sustainability and understory biodiversity conservation (Hartley, 2002;Carnus et al, 2003).…”
Section: Introductionmentioning
confidence: 96%